Characterization of a splice-site mutation in the tumor suppressor gene FLCN associated with renal cancer - Malte P. Bartram; Tripti Mishra; Nadine Reintjes; Francesca Fabretti; Hakam Gharbi; Alexander C. Adam; Heike Göbel; Mareike Franke; Bernhard Schermer; Stefan Haneder; Thomas Benzing; Bodo B. Beck; et al. (BMC, 2017)
Abstract Background Renal cell carcinoma is among the most prevalent malignancies. It is generally sporadic. However, genetic studies of rare familial forms have led to the identification of mutations in causative genes such as VHL and FLCN. Mutations in the FLCN gene are the cause of Birt-Hogg-Dubé syndrome, a rare tumor syndrome which is characterized by the combination of renal cell carcinoma, pneumothorax and skin tumors. Methods Using Sanger sequencing we identify a heterozygous splice-site mutation in FLCN in lymphocyte DNA of a patient suffering from renal cell carcinoma. Furthermore, both tumor DNA and DNA from a metastasis are analyzed regarding this mutation. The pathogenic effect of the sequence alteration is confirmed by minigene assays and the biochemical consequences on the protein are examined using TALEN-mediated transgenesis in cultured cells. Results Here we describe an FLCN mutation in a 55-year-old patient who presented himself with progressive weight loss, bilateral kidney cysts and renal tumors. He and members of his family had a history of recurrent pneumothorax during the last few decades. Histology after tumor nephrectomy showed a mixed kidney cancer consisting of elements of a chromophobe renal cell carcinoma and dedifferentiated small cell carcinoma component. Subsequent FLCN sequencing identified an intronic c.1177-5_-3delCTC alteration that most likely affected the correct splicing of exon 11 of the FLCN gene. We demonstrate skipping of exon 11 to be the consequence of this mutation leading to a shift in the reading frame and the insertion of a premature stop codon. Interestingly, the truncated protein was still expressed both in cell culture and in tumor tissue, though it was strongly destabilized and its subcellular localization differed from wild-type FLCN. Both, altered protein stability and subcellular localization could be partly reversed by blocking proteasomal and lysosomal degradation. Conclusions Identification of disease-causing mutations in BHD syndrome requires the analysis of intronic sequences. However, biochemical validation of the consecutive alterations of the resulting protein is especially important in these cases. Functional characterization of the disease-causing mutations in BHD syndrome may guide further research for the development of novel diagnostic and therapeutic strategies.